Analisis Perputaran Modal Kerja PT. Akasha Wira International, Tbk Tahun 2017-2019 - Pagiu, Chrismesi (UKI Toraja Press, 2021)
This study aims to determine the working capital turnover at PT. Akasha Wira International Tbk in 2017-2019. The data analysis technique used in this research is descriptive quantitative. The results show that the rate of working capital turnover from 2017-2019 has decreased, while for the turnover period it has increased and the level of net sales fluctuates. In 2017, the turnover of working capital was 16.50 times a year with a turnover period of 22 days and sales of IDR 814,490,000,000. In 2018 the turnover of working capital was 7.90 times a year with a turnover period of 45 days and net sales decreased to IDR 804,302,000,000. This is because companies cannot utilize existing working capital to generate maximum net sales. In 2019 the turnover of working capital was 4.74 a year with a turnover period of 72 days and net sales of IDR. 834,330,000,000. Even though their working capital turnover has decreased, the company can take advantage of the existing working capital to increasing net sales.